(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article investigates hypernym-hyponym relationships in Uzbek kitchen utensil terminology, revealing a multi-tiered semantic hierarchy. The study identifies "oshxona anjomlari" (kitchen utensils) as the overarching hypernym encompassing three primary hyponymic categories: containers, kitchen items, and kitchen tools/equipment. The analysis demonstrates two-, three-, and four-level hierarchical structures within the semantic field. Following O.A. Guryanova’s substitution principle, the research confirms that hypernyms can replace hyponyms in discourse but not conversely, as hyponyms contain additional specific semantic features beyond the general meaning of their superordinate terms.